European household waste management schemes: Their effectiveness and applicability in England. - Husaini, I. G.; Garg, A.; Kim, Kye-Hoon; Marchant, J.; Pollard, Simon J. T.; Smith, Richard (Elsevier Science B.V., Amsterdam., 2007)
This paper reviews European household waste management schemes and provides an insight into their effectiveness in reducing or diverting household waste. The paper also considers the feasibility of replicating such schemes in England. Selected case studies include those implemented using variable charging schemes, direct regulation and household incentivisation (reduced disposal charges). A total of 15 case studies were selected from developed countries in the EU where some schemes have operated for more than a decade. Criteria for assessing the effectiveness and replicability of schemes were developed using scheme progress towards targets, response time, compatibility with government policy, ease of administration and operation, and public acceptance as attributes. The study demonstrates the capability of these schemes to significantly reduce household waste and suggests changes to allow their possible adoption in England. One of the main barriers to their adoption is the Environmental Protection Act, 1990 that prevents English local authorities (LAs) from implementing the variable charging method for household waste management. This barrier could be removed through a change in legislation. The need to derive consistent data and standardise the method of measuring the effectiveness of schemes is also highlighted.
Keywords: Household waste; Waste reduction; Waste diversion; Economic instruments; Regulatory instruments; Incentivisation